GoEliTool for Software Requirements Elicitation using Goal-Oriented Approach - Rosa Delima; Joko Purwadi (JEPIN (Jurnal Edukasi dan Penelitian Informatika), 2022)
Requirements engineering (RE) is an essential initial stage in software engineering. The RE process begins with the elicitation stage. This stage collects all user requirements that must be fulfilled by the system which will be developed. A goal-oriented approach is an effective approach used to automate the RE process. The development of goal-oriented input document standards is one of the important issues that has not been widely studied. Therefore, this study developed a goal-oriented input document standard for the requirements elicitation process. A tool is developed based on the form of the input document that has been generated. The development of standard forms of input documents begins with literature study and data collection, analysis, design of standard forms of documents, tool design, tool development, and testing. At the analysis stage, a logical framework and element structure is formulated in a goal-oriented approach. Furthermore, the standard form of input documents is developed. The standard form of the document becomes a guideline for developing tools to process data requirements from elicitation results. Tool testing is carried out using black-box testing. The test results show that the tool can work according to the planned function. The trial of the use of the tools was carried out using five requirements datasets. The results of testing and using the tool through the requirements dataset show that GoEliTools can be used to record data on the requirements of several users for the development of an information system.